ZVONA IZ ARHEOLOŠKOG MUZEJA ISTRE U PULI. - BRADARA, Tatjana (Histria Archaeologica, 2017)
The paper presents information found in the archives of the Documentation Department at the Archaeological Museum of Istria and the documentation of the City Museum of Pazin which to a large extent relates to the restitution of the bells. Information on the bells can be found in the inventory ledger of the Royal Museum of Istria (today's Archaeological Museum of Istria). Special attention is given to the bell of craftsmen Belo and Vivencius from the second quarter of the 14th century, found during archaeological investigations in the basement of the Archaeological Museum of Istria.